1965
DOI: 10.1021/ac60231a024
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Mixtures of Aluminum, Gallium, and Indium by Solvent Extraction and Gas Chromatography.

Abstract: Solvent extraction is combined with gas chromatography to produce an effective method of analysis for aluminum, gallium, and indium mixtures. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
7
0

Year Published

1965
1965
1992
1992

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…The only caveat is that for gallium and indium. These metals have been reported separated by columns bearing heavier loads of coatings, including D.C.-710 used in this work (7,11,12), but an attempt to separate In(tfa)3 from AHtfajs using column 1 was unsuccessful. However, there are two factors which offset any difficulties with this metal and at least one for gallium.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The only caveat is that for gallium and indium. These metals have been reported separated by columns bearing heavier loads of coatings, including D.C.-710 used in this work (7,11,12), but an attempt to separate In(tfa)3 from AHtfajs using column 1 was unsuccessful. However, there are two factors which offset any difficulties with this metal and at least one for gallium.…”
Section: Discussionmentioning
confidence: 86%
“…The chelation of chromium occurs over a broad pH range (5) using a very large excess of chelating agent (6), whereas quantitative aluminum chelate formation requires a pH of about 5.5 (1,7). The chromium chelate is also quantitatively formed at 150-175 °C using a dilute hexane solution of the chelating agent (8), but in this work it was discovered that the aluminum chelate is destroyed at temperatures above 100 °C, with or without a buffer, and at 60-70 °C hexane and cyclohexane are inefficient in the extraction of the chelates, being about 10% low for both metals for a single extraction.…”
Section: Discussionmentioning
confidence: 99%
“…A recent monograph by Moshier and Sievers (IS) summarizes the advances made in this field; the reader is referred to this work for a bibliography and historical description. Other pertinent studies that have been reported since the monograph was written are those of Morie and Sweet (10), Moshier and Schwarberg (11), and Scribner, et al (17,18).…”
mentioning
confidence: 99%
“…Practical application of these GLC methods requires some means for converting a sample into an organic solution containing the beryllium chelate. Solvent extraction of aqueous solutions of copper, iron, aluminum, gallium, indium, and scandium with an organic solution of trifluoroacetylacetone has been successfully employed to prepare solutions suitable for injection into a gas chromatograph (3,5,6,11,12). Beryllium acetylacetonate can also be eluted from a gas-liquid chromatographic column (1).…”
mentioning
confidence: 99%